COUNTRY OF ORIGIN EFFECTS AND CONSUMER PRODUCT EVALUATION PROCESS - Afnan Hossain, Md (British Journal of Marketing Studies, 2015)
The topic is focused on country of origin concept and its impact on consumer product evaluation process. In analyzing, attempt was made from cognitive perspective of country of origin and the processing of consumers prior knowledge about a country’s products and not about the country itself. The analysis reveals that the occurrence of a country of origin-effect in terms of a halo effect, a summary-construct effect, a product attribute effect of a default heuristic effect on the consumer’s evaluative tendency.